2004
DOI: 10.1196/annals.1298.019
|View full text |Cite
|
Sign up to set email alerts
|

Song and the Limbic Brain: A New Function for the Bird's Own Song

Abstract: The neurobiological investigation of the avian song system has largely focused on the unique neural features of vocal control systems that contribute to learned motor patterns in songbirds. The role of emotion has been disregarded in developing a theory of song learning and performance. Here we review emerging evidence in support of Darwin's observation that vocal communication is emotional expression. We propose that neural pathways mediating emotional state remained integrated with the vocal control system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Thus, studies in humans as well as in many other animal species suggest to us the reasonable notion that variations in AVPR1a microsatellite structure might also predispose some individuals to excel in dancing. Darwin observed that vocalization is a form of emotional expression, but among neuroethologists, questions concerning the role of emotion in vocal (and dance) communication have been superseded by questions that concern sensorimotor integration [64]. We believe that the two genes we have identified with dancing in humans are likely involved in the emotional side of dance rather than in the sensorimotor mechanics of this complex phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, studies in humans as well as in many other animal species suggest to us the reasonable notion that variations in AVPR1a microsatellite structure might also predispose some individuals to excel in dancing. Darwin observed that vocalization is a form of emotional expression, but among neuroethologists, questions concerning the role of emotion in vocal (and dance) communication have been superseded by questions that concern sensorimotor integration [64]. We believe that the two genes we have identified with dancing in humans are likely involved in the emotional side of dance rather than in the sensorimotor mechanics of this complex phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…Hypothalamic lesion outside of this region, such as in the lateral hypothalamus, did not affect cooing behavior (Bernstein et al, 1993;Gibson and Cheng, 1979). Interestingly, although lesion in the midbrain ICo vocal pathway disrupts both the bow coo and the nest coo, VMN lesion affects only the nest coo (Cohen, 1981;Cohen and Cheng, 1982;Bernstein et al, 1993;Cheng and Durand, 2004). The rapid recovery of the bow coo after VMN lesion suggests that general debilitation associated with the surgical procedure rather than specific neuronal loss was the culprit.…”
Section: Relationship Between Neurogenesis and Behavioral Recoverymentioning
confidence: 91%
“…1, available at www.jneurosci.org as supplemental material). There are several reasons for hypothesizing a role for auditory input: (1) neurons in several song nuclei show auditory responses to song stimuli in awake and/or anesthetized or sleeping birds, with pronounced selectivity for a bird's own song (for review, see Theunissen et al, 2004); (2) vocalizations are important in coordinating the timing of reproduction in birds (for review, see Cheng and Durand, 2004); (3) auditory feedback is necessary for the juvenile development of song, and its adult maintenance in some species (for review, see Woolley, 2004); (4) auditory information modifies expression of several activity-dependent genes (e.g., ZENK, c-fos, Arc) in telencephalic auditory regions and the song nuclei (for review, see Mello et al, 2004); and (5) auditory input increases CREB phosphorylation in HVC neurons and immunostaining for protein kinase C (PKC) in RA of zebra finches and Bengalese finches (Sakaguchi and Yamaguchi, 1997;Sakaguchi et al, 1999;Watanabe et al, 2002).…”
Section: Introductionmentioning
confidence: 99%